2007
DOI: 10.1063/1.2430933
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-laser deposited LiNi0.8Co0.15Al0.05O2 thin films for application in microbatteries

Abstract: Li Ni 0.8 Co 0.15 Al 0.05 O 2 thin films were prepared by pulsed-laser deposition at varying growth conditions. It was found that the growth and microstructure of the films is highly dependent on the target composition, deposition temperature, and the reactive atmosphere during laser ablation. The x-ray diffraction and Raman spectroscopic measurements indicated the high-structural quality of the grown LiNi0.8Co0.15Al0.05O2 thin films. A phase diagram mapping the effect of temperature on the microstructure of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The specific capacities were calculated assuming a density of 4.82 gcm À3 . It has been reported that the optimal growth temperature is 450 C for the pulse laser deposited LiNi 0.8-Co 0.15 Al 0.05 O 2 film electrodes [21]. The initial specific capacities and coulombic efficiency of the thin film electrodes annealed at 400 C can be comparable to those of the thin film electrodes annealed at 450 C. However, the specific capacities decrease fast in the succeeding cycles.…”
Section: Xps Analysis Of Lini 1/3 Co 1/3 Mn 1/3 O 2 Thin Filmsmentioning
confidence: 95%
“…The specific capacities were calculated assuming a density of 4.82 gcm À3 . It has been reported that the optimal growth temperature is 450 C for the pulse laser deposited LiNi 0.8-Co 0.15 Al 0.05 O 2 film electrodes [21]. The initial specific capacities and coulombic efficiency of the thin film electrodes annealed at 400 C can be comparable to those of the thin film electrodes annealed at 450 C. However, the specific capacities decrease fast in the succeeding cycles.…”
Section: Xps Analysis Of Lini 1/3 Co 1/3 Mn 1/3 O 2 Thin Filmsmentioning
confidence: 95%
“…In a second article, Sakamoto et al examined the structural properties of the surface and bulk of LiNi 0.5 Mn 0.5 O 2 epitaxial thin films during an electrochemical reaction using in situ X-ray scattering [109]. In normal conditions, the two-dimensional diffusion of Li during (de)intercalation proceeds for the (110) plane. However, 3D-diffusion activity can be observed for a high degree of cation mixing (Ni 2+ in Li(3a) sites).…”
Section: Lini 1−y Mn Y O 2 (Nmo)mentioning
confidence: 99%
“…The excellent capability of PLD for reactive deposition and to transfer the stoichiometry of the target to the deposited film makes it an attractive choice to fabricate high-quality crystalline oxide films at relatively low temperatures for electrochemical and optical applications. [15][16][17][18] A comparative study of the films grown using PLD and sputtering could be useful to optimize the conditions to produce large-area Mo oxide films with excellent quality and structural stability. Therefore, the grown Mo oxide films using PLD and sputtering were characterized to obtain information on the surface structure, topography, composition, phase, and morphology.…”
Section: Introductionmentioning
confidence: 99%